Characterization of Plebeiobacterium marinum gen. nov., sp. nov. and Plebeiobacterium sediminum sp. nov., revealing the potential nitrogen fixation capacity of the order Marinilabiliales - Yu, Wen-Xing; Liang, Qi-Yun; Du, Zong-Jun; Mu, Da-Shuai (Frontiers in Marine Science, 2023)
Biological nitrogen fixation plays a crucial role in the marine nitrogen cycle, impacting global marine productivity and related carbon fluxes. Through gene annotation, it was revealed that strains D04 T and AAT T contain a set of nif gene clusters responsible for nitrogen fixation. These two strains were isolated from the coastal sediment at Xiaoshi Island in Weihai, China, and are yellow-colored, Gramstain-negative, facultatively anaerobic, and rod-shaped bacteria. The optimal growth conditions for strain D04 T were found to be at 33 °C, pH 7.0, and in 2% (w/v) NaCl, while strain AAT T prefers growth conditions at 33 °C, pH 6.5, and in 3% (w/v) NaCl. Phylogenetic analysis of the 16S rRNA gene sequences indicated that the highest similarity of strains D04 T and AAT T was to Saccharicrinis fermentans NBRC 15936 T , with a similarity of 94.1% and 94.8%, respectively. The 16S rRNA gene sequence similarity between the two strains was 96.6%. In addition to their growth conditions and phylogenetic analysis, we present a detailed description of the physiological, genomic, and metabolic traits of strains D04 T and AAT T . These novel strains were found to represent new taxa of the Marinilabiliaceae family, and we propose the names Plebeiobacterium marinum gen. nov., sp. nov. and Plebeiobacterium sediminum sp. nov. with type strains D04 T (MCCC 1H00493 T = KCTC 92026 T ) and AAT T (MCCC 1H00485 T = KCTC 92028 T ), respectively. In this study, nitrogen-fixation genes were predicted for fifty-three strains from the whole order Marinilabiliales and found that nitrogen fixation gene clusters were present in twenty-six strains. These gene clusters were found in every family in the order, highlighting that the presence of nitrogen-fixing gene clusters in the order is common. Nitrogen-fixing bacteria in sediments play an important role in various biogeochemical cycles. Thus, understanding the oceanic nitrogen cycle can provides insight into the energy flow of the marine systems.